Modelling the economy and the environment (New York, 1996)
This book presents leading -edge research in environmental-economic modelling currently being undertaken in Scandinavia. There is a strong economic modelling tradition in Scandinavia and Scandinavian countries are well known for their interest in environment questions. This combination has produced fruitful results. Special attention is given to modelling in the agricultural, transport and energy sectors
Keywords: agriculture - environment aspects,controlled ecological systems ( space environment )